2022
DOI: 10.1101/2022.07.06.22277306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Duration of immune protection of SARS-CoV-2 natural infection against reinfection in Qatar

Abstract: BACKGROUND: The future of the SARS-CoV-2 pandemic hinges on virus evolution and duration of immune protection of natural infection against reinfection. We investigated duration of protection afforded by natural infection, the effect of viral immune evasion on duration of protection, and protection against severe reinfection, in Qatar, between February 28, 2020 and June 5, 2022. METHODS: Three national, matched, retrospective cohort studies were conducted to compare incidence of SARS-CoV-2 infection and COVID-1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Infection-acquired immunity boosted with vaccination remained high more than 1 year after infection 27 . A study performed in Qatar reported that effectiveness of Pfizer vaccination against symptomatic BA.2 infection with two doses of Pfizer vaccine was negligible 28 , in agreement with our observation of a lack of detection Nabs against Omicron variants in sera from double vaccine recipients. The effectiveness of three doses of Pfizer, without or with previous infection was 52 % and 77%, respectively 28 .…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Infection-acquired immunity boosted with vaccination remained high more than 1 year after infection 27 . A study performed in Qatar reported that effectiveness of Pfizer vaccination against symptomatic BA.2 infection with two doses of Pfizer vaccine was negligible 28 , in agreement with our observation of a lack of detection Nabs against Omicron variants in sera from double vaccine recipients. The effectiveness of three doses of Pfizer, without or with previous infection was 52 % and 77%, respectively 28 .…”
supporting
confidence: 92%
“…A study performed in Qatar reported that effectiveness of Pfizer vaccination against symptomatic BA.2 infection with two doses of Pfizer vaccine was negligible 28 , in agreement with our observation of a lack of detection Nabs against Omicron variants in sera from double vaccine recipients. The effectiveness of three doses of Pfizer, without or with previous infection was 52 % and 77%, respectively 28 . Another report from USA indicated that vaccine effectiveness against COVID-19–associated hospitalization was higher during the BA.1 period than during the BA.2/BA.2.12.1 period 29 .…”
supporting
confidence: 92%
“…Hence, partial immune evasion can lead to a lower titre of neutralizing antibodies that, with a similar slope of decline, will tend to be faster in reaching a level of neutralizing antibodies unable to sustain protection from infection. The relationship between immune evasion and more rapid waning was well illustrated for omicron subvariants 10 . Still, the protection that we are calculating is the protection relevant for public health since infection with previous variants occurred at different times in the past.…”
Section: Resultsmentioning
confidence: 93%
“…High levels of SARS-CoV-2 antibodies are associated with a lower infection risk and severe COVID-19 [1][2][3][4][5][6]. However, the level of protection is not assumed to be identical for all viral variants [7][8][9][10] and multiple factors contribute to the degree of individual immune response, such as age [11,12], sex [11,12], the variant which caused an infection [13,14], the severity of infection [15,16], vaccine products [17][18][19], and the inter-dose interval [20,21], among others. Furthermore, protection against SARS-CoV-2 infection diminishes over time as anti-SARS-CoV-2 antibodies wane [10,11,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the level of protection is not assumed to be identical for all viral variants [7][8][9][10] and multiple factors contribute to the degree of individual immune response, such as age [11,12], sex [11,12], the variant which caused an infection [13,14], the severity of infection [15,16], vaccine products [17][18][19], and the inter-dose interval [20,21], among others. Furthermore, protection against SARS-CoV-2 infection diminishes over time as anti-SARS-CoV-2 antibodies wane [10,11,22]. Therefore, continuous monitoring of the seroprevalence of antibodies is important to help appraising the latest immune status in the population.…”
Section: Introductionmentioning
confidence: 99%